Scepticism and belief in English witchcraft drama, 1538-1681 - Pudney, Eric (Lund University Press, 2019)
This book situates witchcraft drama within its cultural and intellectual context, highlighting the centrality of scepticism and belief in witchcraft to the genre. It is argued that these categories are most fruitfully understood not as static and mutually exclusive positions within the debate around witchcraft, but as rhetorical tools used within it. In drama, too, scepticism and belief are vital issues. The psychology of the witch character is characterised by a combination of impious scepticism towards God and credulous belief in the tricks of the witch's master, the devil. Plays which present plausible depictions of witches typically use scepticism as a support: the witch's power is subject to important limitations which make it easier to believe. Plays that take witchcraft less seriously present witches with unrestrained power, an excess of belief which ultimately induces scepticism. But scepticism towards witchcraft can become a veneer of rationality concealing other beliefs that pass without sceptical examination. The theatrical representation of witchcraft powerfully demonstrates its uncertain status as a historical and intellectual phenomenon; belief and scepticism in witchcraft drama are always found together, in creative tension with one another.